Hitler sites : a city-by-city guidebook (Austria, Germany, France, United States) - Lehrer, Steven 1944- (McFarland, 2002)
Machine generated contents note: I. AUSTRIA -- Upper and Lower Austria -- Vienna -- Hitler's Lodgings in Vienna -- II. GERMANY -- Munich: City Center -- Munich: Brienner Strasse Corridor -- Munich: East of the Isar River -- Munich: Sites Associated with the Beer Hall Putsch -- Landsberg am Lech -- Berlin -- The Berlin Bunkers -- Potsdam -- Schorfheide -- Bayreuth -- Berchtesgaden -- Nuremberg -- Wunsiedel -- Hitler's Field Headquarters -- The Autobahn ("Streets of the Fiihrer") -- The Siegfried Line (Westwall) -- III. FRANCE -- The Maginot Line -- Compigne -- Paris -- Lyon -- IV. UNITED STATES -- New York City